Power objects in Tibetan Buddhism: the life, writings, and legacy of Sokdokpa Lodrö Gyeltsen - Gentry, James Duncan (Brill's Tibetan studies library, 2017)
In 'Power Objects in Tibetan Buddhism: The Life, Writings, and Legacy of Sokdokpa Lodro Gyeltsen', James Duncan Gentry explores how objects of power figure in Tibetan religion, society, and polity through a study of the life of the Tibetan Buddhist ritual specialist Sokdokpa Lodrö Gyeltsen (1552-1624) within the broader context of sixteenth- and seventeenth-century Tibet. In presenting Sokdokpa's career and legacy, Gentry traces the theme of power objects across a wide spectrum of genres to show how Tibetan Buddhists themselves have theorized about objects of power and implemented them in practice. This study therefore provides a lens into how power objects serve as points of convergence for elite doctrinal discourses, socio-political dynamics, and popular religious practices in Tibetan Buddhist societies